Analisis Efektivitas Latihan Otot Wajah dalam Mencegah dan Memperbaiki Penurunan Wajah pada Pasien Stroke Non-Hemoragik di Ambon, Maluku: Sebuah Studi Klinis - Hernita Frisnawati Purba; Fiktoria Titirlolobi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to evaluate the effectiveness of facial muscle exercises in preventing and improving facial droop in non-hemorrhagic stroke patients. The sample size is 30 individuals selected using purposive sampling and divided into intervention or control groups. Facial symmetry assessment uses the Sunnybrook Facial Grading System. Effectiveness will be evaluated by comparing pre- and post-intervention results and comparing with the control group that did not exercise. The study results show that the intervention group significantly improved their average score to 68.7. In contrast, the control group showed no score change, remaining at 49.3. The average score improvement in the intervention group is 21.4 points, while there is no improvement in the control group. Facial muscle exercises applied to the intervention group effectively enhance facial symmetry and function in patients with facial paralysis. Based on the study's findings, it is recommended to develop clinical practice by incorporating facial muscle exercises in treating patients with facial droop.